My Father’s Daughter: Family Traits and Family Folklore - Gould, Jillian (Ethnologies, 2024)
This personal reflection considers how stories that we share within our families not only inform (and define) worldview, but also “family traits” that may be transmitted through the telling of these stories or anecdotes. In particular, I consider how my father’s approaches and attitudes towards work and leisure were conveyed to me not only through stories, but also by observation—attitudes and ways that in turn shaped my own.